2005
DOI: 10.1152/ajpcell.00348.2004
|View full text |Cite
|
Sign up to set email alerts
|

Inversion of both gating polarity and CO2 sensitivity of voltage gating with D3N mutation of Cx50

Abstract: The effect of CO 2-induced acidification on transjunctional voltage (Vj) gating was studied by dual voltage-clamp in oocytes expressing mouse connexin 50 (Cx50) or a Cx50 mutant (Cx50-D3N), in which the third residue, aspartate (D), was mutated to asparagine (N). This mutation inverted the gating polarity of Cx50 from positive to negative. CO2 application greatly decreased the Vj sensitivity of Cx50 channels, and increased that of Cx50-D3N channels. CO2 also affected the kinetics of Vj dependent inactivation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 41 publications
(59 reference statements)
2
27
0
Order By: Relevance
“…For example, replacement of Asp3 with asparagine in Cx50 also resulted in an inversion of the polarity of V j gating [35]. Interestingly, this substitution also affects the sensitivity of Cx50 channels to CO 2 [35]. …”
Section: Roles Of Nt Amino Acids In Channel Gating Unitary Conducmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, replacement of Asp3 with asparagine in Cx50 also resulted in an inversion of the polarity of V j gating [35]. Interestingly, this substitution also affects the sensitivity of Cx50 channels to CO 2 [35]. …”
Section: Roles Of Nt Amino Acids In Channel Gating Unitary Conducmentioning
confidence: 99%
“…It is interesting that the critical residues implicated in determining these various physiological properties are among the most divergent amino acids within the NT domain (see [26, 32, 35]). Although overall the sequence of this domain is quite conserved, the substitutions confer many of the characteristic properties that differentiate channels formed of different connexins.…”
Section: Roles Of Nt Amino Acids In Channel Gating Unitary Conducmentioning
confidence: 99%
“…Intracellular pH of the oocytes was measured as described by Sasaki et al (1992) and Peracchia and Peracchia (2005). Briefly, the fluorescein derivative pH indicator BCECF B-1151 (Molecular Probes, Eugene, OR, USA) was injected into oocytes in amounts sufficient to reach an intraoocyte concentration of 100 lM (Peracchia and Peracchia 2005).…”
Section: Internal Ph Measurementmentioning
confidence: 99%
“…Briefly, the fluorescein derivative pH indicator BCECF B-1151 (Molecular Probes, Eugene, OR, USA) was injected into oocytes in amounts sufficient to reach an intraoocyte concentration of 100 lM (Peracchia and Peracchia 2005). After the injection, the oocytes were incubated for 40 min and then placed in a built-in chamber, with the vegetative pole facing the fluorescent beam and held in place using a thin stainless steel wire.…”
Section: Internal Ph Measurementmentioning
confidence: 99%
“…However, the extent and sensitivity of V j -gating of different gap junction channels can vary drastically (Burt and Spray, 1988; Barrio et al, 1991; Verselis et al, 1994; Purnick et al, 2000). Earlier studies on Cx26, Cx32 and other connexins have indicated that among several domains, the NT domain and the residue within the NT domain play a crucial role in gating polarity, the properties of V j -gating and unitary conductance (Rubin et al, 1992; Verselis et al, 1994; Purnick et al, 2000; Musa et al, 2004; Peracchia and Peracchia, 2005; Srinivas et al, 2005; Dong et al, 2006; Gemel et al, 2006; Verselis and Srinivas, 2008; Kronengold et al, 2012). The molecular basis of V j -gating is not fully understood.…”
Section: Introductionmentioning
confidence: 99%